Nitrogen application after plant growth regulator herbicide drift reduces soybean growth and yield. Issue 3 (14th May 2019) - Van de Stroet, Brian; Reicks, Graig; Joshi, Deepak; Subramanian, Sen; Clay, David; Clay, Sharon A.
Abstract: The success of dicamba-tolerant soybean [ Glycine max (L.) Merr.] has revived concerns about plant growth regulator (PGR) herbicide exposure to conventional soybean. In laboratory studies, soybean root nodulation is inhibited by excess auxin, which is the mechanism of action of PGR herbicides. Soybean exposed to PGRs in a field environment may have a similar response, and if nodulation is compromised, nitrogen (N) fixation may be reduced, with subsequent seed yield or protein content decreases. Many soybean–N studies report minimal impact to soybean yield. However, if soybeans show foliar PGR injury symptoms, could N application compensate for a potential nodulation inhibition response? This study examined the response of non–PGR tolerant soybean to N after exposure to low doses of 2, 4-D and dicamba applied once (at soybean growth stages V1, V3, and early reproduction [R1 or R2]) or twice (V1 + V3 or V3 + R). N was either foliar or soil applied at early (∼5 d after PGR application) or late (10 d after PGR application) timings. Nodulation and plant growth were evaluated at R3, and grain yield and seed protein and oil content were quantified at maturity. Plant biomass and nodulation were reduced by 10% with some PGR treatments, and early foliar N application after PGR injury resulted in reduction up to 25%. N applications to non–PGR treated soybean did not increase yield. Soybean treated with PGR at V1 or V3, with or without N, had yields similar to control treatments. However, yield reductions of up to 20% were observed when PGRs were applied at V5 or R stages or when double PGR applications were followed by early foliar N application. Seed protein and oil content were not affected by PGR or N treatment.